Scapulae for shovels: Does raw material choice reflect technological ease and low cost in production?. (September 2018) - Xie, Liye
Abstract: Earth-working spades were crafted from bone, stone, and wood in preindustrial societies. In the early Hemudu culture (7000-6000 BP) in eastern China, bone, particularly wild water buffalo scapulae, was preferred for crafting spades to modify the margins of wetlands for cultivation and occupation. Experimental and ethnographic research show that earth properties in the area adequately explains why wooden spades were less common; however, preference for bone spades over stone spades requires explanations beyond techno-functions during use. This paper identifies potential factors during the manufacturing procedure that might have encouraged the development and persistence of the scapular spade tradition. Replication experiments reconstructed the manufacturing procedure of the Hemudu scapular spade in comparison to that of a groundstone equivalent. The results showed that the manufacture knowledge was sophisticated for bone as well as for stone. However, the adequate level of know-how for successful production was lower for bone. Surprisingly, the costs in time and manufacturing tools for crafting a good enough bone tool were higher than those for a stone counterpart. In fact, the manufacture of bone tools involved the use of advanced groundstone tools. Overall, the Hemudu tool producers appear to have made their technological choices based on traditional conformity as well as resistance to motor skill adjustment rather than comprehensive cost-benefit assessment. The persistence of the scapular spade tradition led to increased investments into sophisticated modifications to cope with increasingly arduous earth-working tasks and likely led to increased investment into raw material procurement when bone raw materials became scarce. The results also suggest that technological ease and manufacturing costs in tool production should be evaluated carefully within the behavioral contexts, while taking into account that implements crafted from a variety of raw materials were employed in manufacturing the tool and that the costs and benefits in production are not equally perceivable to decision makers. Highlights: Success rate for crafting a bone tool is higher than for a stone equivalent. Costs of time and tools for crafting a bone tool is higher than for a stone equivalent. Bone tool production involves the uses of groundstone tools. Conformity and resistance to motor skill adjustment contributed to the persistence of raw material preferences. Infrequent production made the persistence of a tradition enduring even when raw materials were scarce.